Dupilumab Provides Rapid and Sustained Clinically Meaningful Responses in Adults with Moderate-to-severe Atopic Dermatitis - Jonathan I. Silverberg (Society for Publication of Acta Dermato-Venereologica, 2021)
Optimal management of atopic dermatitis requires a comprehensive assessment of response to treatment in order to inform therapeutic decisions. In a real-world setting, successful response to atopic dermatitis treatment is measured by sustained improvements in signs, symptoms, and quality of life. Post-hoc analyses of a 1-year, randomized, double-blinded, placebo- controlled trial (NCT02260986) of dupilumab with concomitant topical corticosteroids in 421 adults with moderate-to-severe atopic dermatitis (of whom 315/106 received placebo/dupilumab (of whom 315 received placebo and 106 received dupilumab) was performed to assess the proportion of responders to dupilumab through a multidimensional composite endpoint. At 6-months, 80.2% of dupilumab-treated vs 40.0% placebo patients (p < 0.0001) achieved improvement in signs (Eczema Area and Severity Index ≤ 7), symptoms (worst itch score ≤ 4), or quality of life (Dermatology Life Quality Index ≤5), representative of minimal/clear atopic dermatitis. All 3 endpoints, indicative of no/minimal atopic dermatitis, were achieved by 44.3% of dupilumab-treated vs 10.2% placebo patients (p < 0.0001) and sustained through 1 year. Dupilumab treatment provided sustained clinically meaningful improvement in signs, symptoms, and quality of life in adults with moderate-to-severe atopic dermatitis.